2021
DOI: 10.14202/vetworld.2021.3126-3131
|View full text |Cite
|
Sign up to set email alerts
|

Detection of invA virulence gene of multidrug-resistant Salmonella species isolated from the cloacal swab of broiler chickens in Blitar district, East Java, Indonesia

Abstract: Background and Aim: The increasing number of multidrug-resistant (MDR) Salmonella species on poultry farms in Indonesia has caused concern regarding human health. This study was conducted to determine the presence of the virulence gene invA in MDR Salmonella species isolated from the cloacal swab of broiler chickens in Blitar district, East Java Province, Indonesia. Materials and Methods: Cloacal swab samples were collected by purposive sampling from 15 farms in four districts. Isolation and identification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Multidrug resistance in Salmonella strains showed various resistant index patterns against the antibiotic classes tested, including beta-lactam, carbapenem, fluoroquinolones, tetracycline, aminoglycosides, sulfonamides, and nitrofurans. The multidrug resistance Salmonella strain isolated in this study showed 75% to 100% susceptibility to fluoroquinolones (ciprofloxacin), carbapenem (imipenem), aminoglycosides (gentamicin) in accordance with the report of Wibisono et al 2021 The multidrug resistance Salmonella isolates in this research were mostly resistant to penicillins (ampicillin), tetracycline, fluoroquinolones (ofloxacin), sulfonamides (sulphamethoxazole/trimethoprim) and nitrofurans (nitrofurantoin) with their resistant ranging from 50% to 100%. The resistant patterns includes; AMP-FT-OFX-SXT-TE; TE-AMP-SXT-FT; AMP-IPM-FT-SXT-TE; AMP-OFX-CTX-FT-SXT-TE; AMP-SXT-CTX-TE; AMP-SXT-TE-CTX-FT; AMP-FT-SXT-TE-C; AMP-CIP-IPM-OFX-TE-CTX; AMP-CTX-OFX-SXT-TE; AMP-FT-OFX-TE-CTX-C. A study conducted in Surabaya, Indonesia, has reported a similar multidrug resistance pattern against Salmonella strains isolated from poultry across three antimicrobial classes such as TE-CIP-SXT, TE-CHL-SXT, and four antimicrobial classes ATM-TE-CIP-CHL -SXT, TE-CIP-CHL-SXT (Fanissa et al 2022).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Multidrug resistance in Salmonella strains showed various resistant index patterns against the antibiotic classes tested, including beta-lactam, carbapenem, fluoroquinolones, tetracycline, aminoglycosides, sulfonamides, and nitrofurans. The multidrug resistance Salmonella strain isolated in this study showed 75% to 100% susceptibility to fluoroquinolones (ciprofloxacin), carbapenem (imipenem), aminoglycosides (gentamicin) in accordance with the report of Wibisono et al 2021 The multidrug resistance Salmonella isolates in this research were mostly resistant to penicillins (ampicillin), tetracycline, fluoroquinolones (ofloxacin), sulfonamides (sulphamethoxazole/trimethoprim) and nitrofurans (nitrofurantoin) with their resistant ranging from 50% to 100%. The resistant patterns includes; AMP-FT-OFX-SXT-TE; TE-AMP-SXT-FT; AMP-IPM-FT-SXT-TE; AMP-OFX-CTX-FT-SXT-TE; AMP-SXT-CTX-TE; AMP-SXT-TE-CTX-FT; AMP-FT-SXT-TE-C; AMP-CIP-IPM-OFX-TE-CTX; AMP-CTX-OFX-SXT-TE; AMP-FT-OFX-TE-CTX-C. A study conducted in Surabaya, Indonesia, has reported a similar multidrug resistance pattern against Salmonella strains isolated from poultry across three antimicrobial classes such as TE-CIP-SXT, TE-CHL-SXT, and four antimicrobial classes ATM-TE-CIP-CHL -SXT, TE-CIP-CHL-SXT (Fanissa et al 2022).…”
Section: Discussionsupporting
confidence: 85%
“…Chicken meats, such as broiler chickens and laying hens, are included as one of the livestock products that are widely consumed. However, it is a primary medium for the spread of the foodborne disease caused by Salmonella infection (Salmonellosis) through the food production chain (Sin et al 2020;Wibisono et al 2021). In Nigeria, Salmonella infections can be transmitted through contaminated poultry feeds, dust, the presence of carriers (rodents and insects), water, contact with the infected birds/feces, animal-tohuman contact, from poor or unclean poultry farms by the poultry workers that can quickly spread to the environment either by human contact or consumption of contaminated poultry meat (Jibril et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The Salmonella spp. were isolated using conventional methods and followed the protocols recommended by the Food and Drug Administration Agency Briefly, within the first step, the collected samples were homogenized with 10 mL of selenite cystine broth (Merck, Bucharest, Romania) for 5 min, according to ISO 6579 [51]. The mixture was then incubated at 35 • C in an aerobic atmosphere for 24 h. Next, one milliliter from each pre-enriched sample after the incubation period was added to 10 mL of BD Rappaport Vassiliadis broth (BD Diagnostic Systems, Heidelberg, Germany) and mixed for 2 min, then subsequently incubated in the aerobic atmosphere for 24 h at 42 • C. After incubation, the tube content was stirred and inoculated on BD MacConkey agar II plates (BD Diagnostic Systems, Heidelberg, Germany) with a bacteriological inoculation loop.…”
Section: Bacterial Isolationmentioning
confidence: 99%
“…The serotyping of the Salmonella isolates was achieved in a pure culture based on the evidence of somatic (O) and flagellar (H) antigens through reactions with specific antisera [51,54]. Salmonella O and Salmonella H antisera (SSI Diagnostica A/S, Hillerød, Denmark) were used according to the manufacturer's recommendations.…”
Section: Serotyping Via Slide Agglutination (Kauffmann-white-le-minor...mentioning
confidence: 99%
“…This review clearly illustrates that in the context of One Health, genomic analysis can reveal opportunities for timely intervention and prevention of the spread of AMR. Another important One Health strategy is the prevention of infection and disease related to APEC and other poultry pathogens [32,121,171,172] by organizing coordinated scientific and public health efforts, ensuring effective surveillance, research, public education, communication, and new policymaking resolutions [173].…”
Section: One Health Approach For Apecmentioning
confidence: 99%